2011
DOI: 10.1167/iovs.10-6985
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Oximetry in Primary Open-Angle Glaucoma

Abstract: PURPOSE. To determine whether retinal vessel oxygen saturation is affected in primary open-angle glaucoma (POAG) patients. METHODS. Retinal oxygen saturation in patients with POAG was measured in retinal vessels with a spectrophotometric retinal oximeter in darkness, and visual fields were obtained. Oxygen tension (Po(2)) was calculated from oxygen saturation values. Statistical analysis was performed using Pearson's correlation and Student's t-test. RESULTS. Mean oxygen saturation in venules was higher in per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 46 publications
7
132
1
1
Order By: Relevance
“…16 Olafsdottir et al 27 reported significantly higher retinal venular oxygen saturations using the same retinal oximeter in glaucomatous eyes with 'poor visual fields' compared with 'good visual fields', 68% ( ± 4%) and 62% ( ± 3%), respectively. Importantly, an earlier study by Hardarson et al 16,27 found comparatively lower retinal mean (±SD) venous oxygen saturation in normal subjects of 55% (±14%). A commonly accepted limitation of the two-wavelength oximetry technique is the tendency to overestimate the true blood oxygen saturation particularly at lower oxygen saturations.…”
Section: Discussionmentioning
confidence: 84%
“…16 Olafsdottir et al 27 reported significantly higher retinal venular oxygen saturations using the same retinal oximeter in glaucomatous eyes with 'poor visual fields' compared with 'good visual fields', 68% ( ± 4%) and 62% ( ± 3%), respectively. Importantly, an earlier study by Hardarson et al 16,27 found comparatively lower retinal mean (±SD) venous oxygen saturation in normal subjects of 55% (±14%). A commonly accepted limitation of the two-wavelength oximetry technique is the tendency to overestimate the true blood oxygen saturation particularly at lower oxygen saturations.…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, in all examined eyes arteriolar oxygen saturation and the retinal arteriovenous differences in oxygen correlated strongly with the patient's rim area. Olafsdottir et al found that deeper VF defects in patients with POAG were associated with decreased arteriovenous difference in retinal oxygen saturation and increased oxygen saturation in venules [86]. No correlation was present concerning retinal arterioles and VF defects.…”
Section: Retinal Blood Flow Alterations and Visual Functionmentioning
confidence: 98%
“…[9][10][11][12] Furthermore, impairment in ocular blood flow has been implicated in disease states such as diabetes, [31][32][33][34] glaucoma, 35,36 and other ocular diseases. 37 It is crucial for any automatic analysis of the retinal blood vessels that the extraction of these vessels is both possible and accurate enough, Table 3 The effect of diabetic retinopathy, hypertension, AMD, or glaucoma on accuracy, sensitivity, specificity, and kappa statistic for the IB and Gabor filter algorithms.…”
Section: Discussionmentioning
confidence: 99%